2013
DOI: 10.1242/jeb.081323
|View full text |Cite
|
Sign up to set email alerts
|

Novel locomotor muscle design in extreme deep-diving whales

Abstract: SUMMARYMost marine mammals are hypothesized to routinely dive within their aerobic dive limit (ADL). Mammals that regularly perform deep, long-duration dives have locomotor muscles with elevated myoglobin concentrations that are composed of predominantly large, slow-twitch (Type I) fibers with low mitochondrial volume densities (V mt ). These features contribute to extending ADL by increasing oxygen stores and decreasing metabolic rate. Recent tagging studies, however, have challenged the view that two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
82
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 62 publications
11
82
2
Order By: Relevance
“…Indeed, comparisons between the pelagic spinner dolphin and coastal bottlenose dolphin indicated that myoglobin contents of the pelagic species were consistently higher than the corresponding age class of the coastal species (Table 2). Furthermore, the myoglobin levels (range from 6.00 to 7.10 g Mb per 100 g wet muscle mass) of adult pelagic delphinids [spinner ( present study) and Fraser's dolphin, Lagenodelphis hosei (Dolar et al, 1999)] fall within the range (6.82-7.41 g Mb per 100 g wet muscle mass) measured for deepdiving cetaceans, such as short-finned pilot whales (Globicephala macrorhynchus; Velten et al 2013) and Gervais' beaked whales (Mesoplodon europaeus; Velten et al 2013). Myoglobin levels of adult pelagic delphinids also fall within the range (6.91-7.87 g Mb per 100 g wet muscle mass) reported for adult Arctic dwelling cetaceans, such as the narwhal (Monodon Monoceros; Williams et al, 2011) and beluga whale (Noren and Suydam, 2016), that must transit under sea ice.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, comparisons between the pelagic spinner dolphin and coastal bottlenose dolphin indicated that myoglobin contents of the pelagic species were consistently higher than the corresponding age class of the coastal species (Table 2). Furthermore, the myoglobin levels (range from 6.00 to 7.10 g Mb per 100 g wet muscle mass) of adult pelagic delphinids [spinner ( present study) and Fraser's dolphin, Lagenodelphis hosei (Dolar et al, 1999)] fall within the range (6.82-7.41 g Mb per 100 g wet muscle mass) measured for deepdiving cetaceans, such as short-finned pilot whales (Globicephala macrorhynchus; Velten et al 2013) and Gervais' beaked whales (Mesoplodon europaeus; Velten et al 2013). Myoglobin levels of adult pelagic delphinids also fall within the range (6.91-7.87 g Mb per 100 g wet muscle mass) reported for adult Arctic dwelling cetaceans, such as the narwhal (Monodon Monoceros; Williams et al, 2011) and beluga whale (Noren and Suydam, 2016), that must transit under sea ice.…”
Section: Discussionsupporting
confidence: 70%
“…Currently, this class of deep-diving odontocete is considered unique in terms of the comparatively high levels of muscle myoglobin in the skeletal muscle as well as the high proportion of body mass composed of muscle (Velten et al, 2013). To account for this, we assumed that skeletal muscle mass of the Cuvier's beaked whale was proportionately the same as reported for other deep-diving beaked whales (48% of body mass) and that myoglobin content was 73.4 g Mb kg −1 muscle (Velten et al, 2013). Multiplying by the oxygen carrying capacity of mammalian myoglobin (1.34 ml O 2 g -1 Mb) results in 118 liters of O 2 available in the beaked whale's skeletal muscles.…”
Section: Oxygen Stores Of Beaked Whalesmentioning
confidence: 99%
“…Multiplying by the oxygen carrying capacity of mammalian myoglobin (1.34 ml O 2 g -1 Mb) results in 118 liters of O 2 available in the beaked whale's skeletal muscles. This muscle oxygen store is only a portion of the total body oxygen store of the odontocete, which ranges from 30% of the total store (Noren and Williams, 2000) to 54% (Velten et al, 2013); we used a mean value of 40% as the conservative estimate for this study, with a resulting total body oxygen store of 295 liters of O 2 for a 2500 kg Cuvier's beaked whale.…”
Section: Oxygen Stores Of Beaked Whalesmentioning
confidence: 99%
“…Two fibre types are found in the musculature of fish : slow-twitch oxidative fibres (red muscle or Type I) are used for slow steady swimming, while fast-twitch fibres (white muscle or Type II) are recruited to power brief bursts of fast swimming during predator avoidance or prey capture (Alexander and Goldspink, 1977). Type I and II muscle fibres are also present in the swimming muscles of marine mammals but less is known about how these are employed (Kanatous et al, 2008;Velten et al, 2013). It is generally assumed that diving mammals minimize their reliance on anaerobic metabolism by choosing dive durations in keeping with their activity levels (Butler and Jones, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Like other deep-diving marine mammals, beaked whales also have physiological adaptations that prolong their ADL: high lipid volume density and myoglobin concentrations increase oxygen stores while extremely low mitochondrial volume densities and large fibre diameters reduce the metabolic rate (Velten et al, 2013;Davis, 2014). Nonetheless, it is likely that the two smallest ziphiid species studied to date, Cuvier's and Blainville's beaked whales, routinely dive beyond their ADL, powering some portion of locomotion in deep dives anaerobically Velten et al, 2013). Despite this, both species make distinctive and enigmatic low-pitch ascents from deep dives.…”
Section: Introductionmentioning
confidence: 99%